Selected Immunological Mediators and Cervical Microbial Signatures in Women with Chlamydia trachomatis Infection - Simone Filardo (American Society for Microbiology, 2019)
ABSTRACT In the female genital ecosystem, the complex interplay between the host immune system and the resident microflora protects against urogenital pathogens, like Chlamydia trachomatis. C. trachomatis is responsible for urethritis and cervicitis; however, most chlamydial infections are asymptomatic and, thus, not treated, potentially leading to severe reproductive sequelae. Here we investigated the interaction between the levels of selected immune mediators and the community state types of the cervical microbiota in C. trachomatis-infected women. Cervical samples from 42 C. trachomatis-positive women and 103 matched healthy controls were analyzed through the metagenomic analysis of the hypervariable region v4 of the 16S rRNA gene and the determination of lactoferrin, interleukin 1α (IL-1α), IL-6, alpha interferon (IFN-α), IFN-β, and IFN-γ by ELISA. Overall, C. trachomatis infection was significantly associated with a microbiota dominated by anaerobic bacteria (P = 0.000002). In addition, a network of Gardnerella vaginalis, Prevotella amnii, Prevotella buccalis, Prevotella timonensis, Aerococcus christensenii, and Variovorax guangxiensis has been identified as a potential biomarker of C. trachomatis infection through multiple statistical approaches. Again, chlamydial infection was significantly correlated with an increased production of lactoferrin, IL-6, IL-1α, IFN-α, and IFN-β (P < 0.05), whereas very low levels of IFN-γ were observed in C. trachomatis-infected women, levels similar to those detected in healthy women. Our findings show a distinctive signature of C. trachomatis genital infection, characterized by a specific bacterial network, constituted by anaerobes, as well as by increased levels of lactoferrin and proinflammatory cytokines (IL-1α, IL-6, IFN-α, and IFN-β), accompanied by low levels of IFN-γ. IMPORTANCE To our knowledge, this is the first study that investigated the association of C. trachomatis with the cervical levels of lactoferrin and selected inflammatory mediators and their correlation with the different community state types characterizing the female genital ecosystem. C. trachomatis, known as the leading cause of bacterial sexually transmitted diseases, continues to be an important public health problem worldwide for its increasing incidence and the risk of developing severe reproductive sequelae, like pelvic inflammatory disease and infertility. Specifically, C. trachomatis tend to persist in the female genital tract, leading to a chronic inflammatory state characterized by increased production of immune mediators responsible for tissue damage. Therefore, our study may help to broaden the knowledge on the complex interplay between the female genital microbiota and the host immune system in response to C. trachomatis infection.